Bio-Priming with Trichoderma spp. to Suppress Aspergillus flavus, the Causal Agent of Damping-off Disease in Peanuts - Anita, Tri Yuli; Suryaminarsih, Penta; Rahmadhini, Noni (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Aspergillus flavus is a fungus that produces aflatoxin, a toxic compound that can contaminate food products, especially nuts. The impact caused by A. flavus causes significant losses for peanut-producing countries in cases of international trade. A. flavus infection in peanuts causes physical changes and quality, as well as a decrease in seed germination. Environmentally friendly control efforts for A. flavus can be carried out by utilizing biological agents such as Trichoderma spp. This study aims to evaluate the ability of T. harzianum and T. asperellum to inhibit the growth of A. flavus. This study also evaluates bio-priming methods enriched with Trichoderma spp. to optimize peanut seed germination. Methods: The research used a factorial Completely Randomized Design (CRD) of 2 factors. The first factor is the isolate species Trichoderma spp. namely T. harzianum (T1), T. asperellum (T2), and Control (T0), namely A. flavus without biological control treatment. The second factor is the application method, which includes the bio-priming (B1) and bio-matrixpriming (B2) methods. Each treatment combination was repeated 4 times, and the number of seeds used was five in each unit. Results: T. harzianum showed the highest inhibitory ability against A. flavus in the in vitro test, namely 49%. Bio-priming treatment containing the active ingredient T. harzianum is the best treatment for increasing peanut germination by 95%. Conclusions: The research results showed that bio-priming treatment with the active ingredient T. harzianum increased the germination rate significantly compared to other treatments.